Chapter Christian Neoplatonism – the Synthesis of Spiritual Traditions of the East and the West - Gensler, Marek (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
Close relations between Christianity and Neoplatonism date back to the very early days of the religion. Although it had its origin in Judaism, it soon found followers among Greeks and Hellenized inhabitants of eastern provinces of the Roman Empire, many of whom had philosophical education. Platonism, reborn in Alexandria, became for Christians a tool useful both for interpreting their own faith and for explaining it to gentiles and soon was seen as an inalienable part of the Christian doctrine on a par with the biblical tradition. The teachings of two eminent thinkers of the Patristic period, Origen and pseudo-Dionysius the Areopagite, both hailing from the Roman East, are examples how Platonic doctrine forms a framework for the religion of Jesus and his disciples.